Optimality conditions in set-valued optimization problems with respect to a partial order relation by using subdifferentials. (4th March 2021) - Karaman, Emrah; Atasever Güvenç, İlknur and Soyertem, Mustafa
Abstract : In this study, set-valued optimization problems are considered with respect to m 1 -order relation, which is a partial order relation on the family of nonempty and bounded sets. Four subdifferentials are defined for set-valued optimization maps. Some existence theorems and relations among these subdifferentials are obtained. By using them, necessary and sufficient optimality conditions are presented for set-valued optimization problems with respect to m 1 -order relation.